2019
DOI: 10.1016/j.jadohealth.2019.02.023
|View full text |Cite
|
Sign up to set email alerts
|

Food Insecurity and Unmet Needs Among Youth and Young Adults Living With HIV in the San Francisco Bay Area

Abstract: Little is known about food insecurity and unmet subsistence needs and their association with antiretroviral therapy adherence among youth and young adults living with HIV (YLWH). Methods: We conducted a cross-sectional survey to examine this association in 101 YLWH (aged 18e29 years). Poisson regression models with robust standard errors were used to estimate adjusted risk ratios (RRs) and 95% confidence intervals (CIs).Results: Approximately 51.7% of participants experienced at least one unmet subsistence nee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…For instance, a recent study of San Francisco, CA youth living with HIV found that recent hunger was experienced by 36.3%. 31 Clearly, however (regardless of the comparison) hunger was disproportionately common in this sample of minority MSM. Second, the number of male partners in the past six months was equally high regardless of hunger.…”
Section: Discussionmentioning
confidence: 71%
“…For instance, a recent study of San Francisco, CA youth living with HIV found that recent hunger was experienced by 36.3%. 31 Clearly, however (regardless of the comparison) hunger was disproportionately common in this sample of minority MSM. Second, the number of male partners in the past six months was equally high regardless of hunger.…”
Section: Discussionmentioning
confidence: 71%
“…GAD scores questions such that a high score (10-21) indicates evidence of anxiety and a score <10 indicates minimal-mild anxiety. PHQ-9 scores depression-related questions that are categorized as ''None'' (0), ''Minimal'' (1-4), ''Mild'' (5-9), ''Moderate'' (10)(11)(12)(13)(14), ''Moderately severe'' (15)(16)(17)(18)(19), and ''Severe'' (20-100). PCL-5 groups the questions as either unlikely to have PTSD (0-32) or high likelihood of having PTSD .…”
Section: Methodsmentioning
confidence: 99%
“…9 Moreover, YLWH may experience other barriers such as unstable housing, food insecurity, low socioeconomic status, and stigma that are often entangled with mental health and substance use challenges and can additionally negatively impact HIV clinical outcomes. 10 Despite the adverse impact that mental health and substance use challenges have on HIV clinical outcomes, there remains a shortage of behavioral health services and evidence-based interventions tailored to YLWH. 5 Although several interventions have been developed to address mental health, substance use, and other psychosocial factors to improve ART adherence for adults, 11,12 few interventions take into account unique aspects of youth developmental phases, culture, and priorities such as technology use.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants and Study Design: We developed the Mobile Technology Vulnerability Scale (MTVS) among 18–29-year-olds living with HIV recruited for a longitudinal pilot trial, evaluating the feasibility and acceptability of a mobile health application called WYZ [ 14 ]. MTVS is analogous to the food insecurity scale [ 15 ] and examines how secure or stable an individual feels regarding their personal access to mobile technology.…”
Section: Methodsmentioning
confidence: 99%